A Bibliometric Review of Environmental Education and Literacy from 2010 to 2021 - Rihhadatul’aysi, Faa’izah Abiyyah (Tauladan Fathimah Azzahra, 2022)
One’s literacy ability is something that should be considered in the era of revolution society 5.0. Environmental literacy is part of basic literacy that is needed so that everyone has the ability to understand and feel that they are part of the solution to environmental problems. This research is a systematic mapping in the topic of ‘environmental literacy’ based on bibliometric analysis. This study aims to determine the development of citations, core journal publications, number of authors, language statistics, publication trends, author collaboration, trend terms keywords, and country statistics on environmental literacy articles in 2010-2021. Data collection through the software used is Publish or Perish (PoP) to search for bibliographies as initial database on Google Scholar. Meanwhile, the country’s statistical data were analyzed using the Vos Viewer. The results showed that the highest number of citations was 761 citations. In the publication trend, the most publications occurred in 2011 with 120 articles. The most widely used keyword term is ‘environmental literacy’ with a frequency of more than 100.